TEKNOLOGI DIGITAL SEBAGAI MEDIA PELAYANAN GEREJA DAN RELEVANSINYA TERHADAP PARTISIPASI KAUM MUDA DALAM BERIBADAH - Anna Paila Meti Kosma Manurung (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2026)
Abstract: The development of digital technology has brought significant changes to various aspects of human life, including the practice of church ministry. The church, as a spiritual institution, is required to adapt to technological developments to remain relevant to its congregation, especially young people living in a digital culture. This study aims to analyze the use of digital technology as a medium for church ministry and its relevance to youth worship participation. The research method used is a descriptive qualitative approach through a literature review of various theological sources and research related to digital technology in church ministry. The results indicate that digital technologies such as social media, online worship broadcasts, and digital Bible applications are effective tools for increasing youth involvement in church life. Digital technology opens up broader participation opportunities for young people in worship, services, and other spiritual activities. However, the use of digital technology must be carried out wisely so as not to diminish the spiritual meaning and fellowship of the congregation. Therefore, churches need to integrate digital technology as a means of supporting their ministry without diminishing the essence of the fellowship of faith.”“Keywords: Digital technology, church ministry, worship participation, youth.”